Proceedings of the 2009 SIAM International Conference on Data Mining 2009
DOI: 10.1137/1.9781611972795.93
|View full text |Cite
|
Sign up to set email alerts
|

Polynomial-Delay and Polynomial-Space Algorithms for Mining Closed Sequences, Graphs, and Pictures in Accessible Set Systems

Abstract: In this paper, we study efficient closed pattern mining in a general framework of set systems, which are families of subsets ordered by set-inclusion with a certain structure, proposed by Boley, Horváth, Poigné, Wrobel (PKDD'07 and MLG'07). By modeling semi-structured data such as sequences, graphs, and pictures in a set system, we systematically study efficient mining of closed patterns. For a class of accessible set systems with a tree-like structure, we present an efficient depth-first search algorithm that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 24 publications
0
46
0
Order By: Relevance
“…In order to provide a generic definition for closed patterns we extend the work of Boley et al (2010) and (Arimura and Uno, 2009). We rely on a homogeneous representation of the patterns and of the dataset using sets.…”
Section: Generic Framework: Definitions and Algorithmic Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to provide a generic definition for closed patterns we extend the work of Boley et al (2010) and (Arimura and Uno, 2009). We rely on a homogeneous representation of the patterns and of the dataset using sets.…”
Section: Generic Framework: Definitions and Algorithmic Backgroundmentioning
confidence: 99%
“…Arimura and Uno (2009) have shown that it is possible to build polynomial-space enumeration strategies if the set system that consists in the ground set and the set of patterns satisfies the property of accessibility.…”
Section: Enumeration Of Closed Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, various mining problems have been investigated that come down to searching for closed motifs which cannot be considered, strictly speaking, as support-closed motifs, such as convex hulls of subsets of a given set of points, or sequential motifs with wildcards. Solving the problem then means defining and building the corresponding closure operator [5]. To characterize such closure operators, the authors make use of a wellknown theorem stating that in a finite lattice T there is a one-to-one correspondence between the families closed under the meet operator and the closure operators on T .…”
Section: Introductionmentioning
confidence: 99%